Direct Evidence of Significantly Different Chemical Behavior and Excited‐State Dynamics of 1, 7‐ and 1, 6‐Regioisomers of Pyrrolidinyl‐Substituted Perylene Diimide. Issue 21 (22nd March 2013) - Dubey, Rajeev K.; Niemi, Marja; Kaunisto, Kimmo; Efimov, Alexander; Tkachenko, Nikolai V.; Lemmetyinen, Helge
Abstract Novel bay‐functionalized perylene diimides with additional substitution sites close to the perylene core have been prepared by the reaction between 1, 7(6)‐dibromoperylene diimide 6 (dibromo‐PDI) and 2‐(benzyloxymethyl)pyrrolidine 5. Distinct differences in the chemical behaviors of the 1, 7‐ and 1, 6‐regioisomers have been discerned. While the 1, 6‐dibromo‐PDI produced the corresponding 1, 6‐bis‐substituted derivative more efficiently, the 1, 7‐dibromo‐PDI underwent predominant mono‐debromination, yielding a mono‐substituted PDI along with a small amount of the corresponding 1, 7‐bis‐substituted compound. By varying the reaction conditions, a controlled stepwise bis‐substitution of the bromo substituents was also achieved, allowing the direct synthesis of asymmetrical 1, 6‐ and 1, 7‐PDIs. The compounds were isolated as individual regioisomers. Fullerene (C60) was then covalently linked at the bay region of the newly prepared PDIs. In this way, two separate sets of perylene diimide–fullerene dyads, namely single‐bridged (SB‐1, 7‐PDI‐C60 and SB‐1, 6‐PDI‐C60) and double‐bridged (DB‐1, 7‐PDI‐C60 and DB‐1, 6‐PDI‐C60), were synthesized. The fullerene was intentionally attached at the bay region of the PDI to achieve close proximity of the two chromophores and to ensure an efficient photoinduced electron transfer. A detailed study of the photodynamics has revealed that photoinduced electron transfer from the perylene diimide chromophore to the fullerene occurs in all four dyads in polar benzonitrile, and also occurs in the single‐bridged dyads in nonpolar toluene. The process was found to be substantially faster and more efficient in the dyads containing the 1, 7‐regioisomer, both for the singly‐ and double‐bridged molecules. In the case of the single‐bridged dyads, SB‐1, 7‐PDI‐C60 and SB‐1, 6‐PDI‐C60, different relaxation pathways of their charge‐separated states have been discovered. To the best of our knowledge, this is the first observation of photoinduced electron transfer in PDI‐C60 dyads in a nonpolar medium.